Predictors of successful inclusion for children with vision impairment in early education - Lane, Cherylee Mary (Curtin University, 2008)
The international movement to include children with disabilities in education has resulted in significant legislative and policy change. However some have argued that this has not translated into actual practice and that inclusion (as opposed to integration) is not the usual practice in Australia. There are fears that inclusion, if implemented poorly, will be detrimental to the wellbeing of students with disabilities. Similar concerns exist for students with vision impairment. The quality of their inclusive experiences varies dramatically from school to school, with an isolated few children reaping the expected benefits of inclusion. The variation in these experiences has not yet been explained.The purpose of this research was to determine which, if any, factors predict successful inclusion for children with vision impairment in regular early education in Australia. The research occurred in two phases: (1) a formative, qualitative phase; and (2) a quantitative, longitudinal phase.The aim of Phase 1 was to select factors that stakeholders perceived were important in influencing the inclusive early education of children with vision impairment in Australia. Nominal Group Technique elicited the perception of five stakeholder groups (allied health professionals, visiting teachers, classroom teachers, parents of, and students with vision impairment) (N = 25). The ranked items generated by each stakeholder group were combined using content analysis. These were then ranked overall. The top-ten ranked ‘stakeholder factors’ formed the independent variables for the second phase of the study.Phase 2 had three aims relating to regular early education in Australia: (1) to describe the situation that children with vision impairment are exposed to (i.e. the stakeholder factors identified in Phase 1); (2) to compare the inclusive outcomes (participation, engagement, child interaction, academic and overall) of children with and without vision impairment; and (3) to determine the influence of the stakeholder factors on the inclusive outcomes of children with vision impairment. A prospective, longitudinal cohort design was used; conducted over two years. Twenty children with vision impairment and 37 sighted classmates (mean age 65 months) who attended regular kindergarten to grade one classes in Australia participated.Three aspects were commonly found to be poor in the regular class situations: access to vision aides and equipment, support for staff, and teacher training and experience; however the individualisation and physical environment were adequate. Nonparametric analysis demonstrated that both education staff and parents were more involved with children with vision impairment compared to classmates. The children’s social skills differed only at the end of the second year.Children with vision impairment had significantly poorer inclusive outcomes than classmates. Mann-Whitney U Tests found that children with vision impairment participated significantly less in class activities, were less engaged in tasks and experienced poorer social interaction than classmates at each point during the two years. At the end of the second year, children with vision impairment had significantly poorer academic performance.A three-step process selected the stakeholder factors that had a significant individual influence on the inclusion of children with vision impairment, relative to their classmates. Receiver Operating Characteristic curve analysis then demonstrated that Indices of these combined stakeholder factors predicted successful inclusive outcomes of children with vision impairment up to two years later. Presence of a combination of at least six factors, categorised as Environmental (teacher attitude, teacher training and experience, adult involvement, vision aides and equipment and physical environment); Personal (early intervention); and/or Activity Performance (social skills) significantly improved the likelihood of success.This study demonstrated that a high proportion of children with vision impairment in Australia are exposed to less than adequate situations in early education, and, as such, experience poor quality inclusion. Given the long term effects of early experiences, it is imperative that children have positive early education experiences. This research provided new knowledge of the factors that can improve regular early educational outcomes for students with vision impairment. This can further guide the decisions of policy makers, educators, health professionals and parents concerned with improving the life of children with vision impairment.